Skew-free parallel optical transmission systems - Fujimoto, N.; Ishizuka, A.; Rokugawa, H.; Mori, K. (Journal of lightwave technology)
This paper proposes two kinds of parallel line codes based on multiplexing and nonmultiplexing, and a method of automatic skew suppression based on bit synchronization and frame synchronization. This achieves parallel high-speed optical transmission to overcome bottlenecks in parallel electronic transmission and to increase the distance of high-throughput interconnections. We have developed GaAs coder/decoder large-scale integrations (LSIs) for the coding algorithm and skew suppression, and analog LSIs for compact, low-power, highspeed parallel optical links. Experimental results show that our proposed parallel transmission methods and fabricated LSIs can play a key role in realizing high-speed, long-distance parallel transmission and in reducing the size and power consumption of high-throughput parallel optical links.